Gene expression profiling in persons with multiple chemical sensitivity before and after a controlled n-butanol exposure session. Issue 2 (22nd February 2017) - Dantoft, Thomas M; Skovbjerg, Sine; Andersson, Linus; Claeson, Anna-Sara; Engkilde, Kaare; Lind, Nina; Nordin, Steven; Hellgren, Lars I
Abstract : Objectives: To investigate the pathophysiological pathways leading to symptoms elicitation in multiple chemical sensitivity (MCS) by comparing gene expression in MCS participants and healthy controls before and after a chemical exposure optimised to cause symptoms among MCS participants. The first hypothesis was that unexposed and symptom-free MCS participants have similar gene expression patterns to controls and a second hypothesis that MCS participants can be separated from controls based on differential gene expression upon a controlled n-butanol exposure. Design: Participants were exposed to 3.7 ppm n-butanol while seated in a windowed exposure chamber for 60 min. A total of 26 genes involved in biochemical pathways found in the literature have been proposed to play a role in the pathogenesis of MCS and other functional somatic syndromes were selected. Expression levels were compared between MCS and controls before, within 15 min after being exposed to and 4 hours after the exposure. Settings: Participants suffering from MCS and healthy controls were recruited through advertisement at public places and in a local newspaper. Participants: 36 participants who considered themselves sensitive were prescreened for eligibility. 18 sensitive persons fulfilling the criteria for MCS were enrolled together with 18 healthy controls. Outcome measures: 17 genes showed sufficient transcriptional level for analysis. Group comparisons were conducted for each gene at the 3 times points and for the computed area under the curve (AUC) expression levels. Results: MCS participants and controls displayed similar gene expression levels both at baseline and after the exposure and the computed AUC values were likewise comparable between the 2 groups. The intragroup variation in expression levels among MCS participants was noticeably greater than the controls. Conclusions: MCS participants and controls have similar gene expression levels at baseline and it was not possible to separate MCS participants from controls based on gene expression measured after the exposure.